Starch Retrogradation: Role of Food Ingredients and Extrinsic Factors - K., Chiravi; A., Khan M.; D., Wadikar D.; C., Mahesh; D., Semwal A. (Food Science and Engineering, 2023)
Starch retrogradation is one of the significant properties of starch wherein the reassociation or recrystallization of the polysaccharides in gelatinized starch (amylose and amylopectin) occurs. Although the process is desirable in terms of nutritional and textural properties for some starchy foods, it tends to exhibit many undesirable effects on storage and sensory qualities of starchy foods. Extensive studies have been done worldwide to understand the in-depth mechanism of retrogradation and its effect on foods. Various factors are involved in hindering/accelerating the retrogradation process thereby influencing the food product properties. This review provides a thorough insight into food constituents as well as extrinsic factors that influence starch retrogradation in food systems. It also explains the role of amylose and amylopectin in retrogradation independently, providing a better understanding to the reader of the retrogradation phenomena.